Investigation on the Performance of Solar Panels as Wind Turbine Blades for Sustainable Power Generation - Nor Zahari, Muhammad Izhar; Bakar , Lilywati; Mustafa, Farahiyah; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2024)
Since the last decade, the world’s population has grown dramatically, resulting in a significant increase in energy demand. The depletion of fossil fuels and environmental issues like global warming necessitate the adoption of renewable energy sources like solar, wind, hydro, and biomass. The main objectives of this research are to study the efficiency and viability employing solar panels as wind turbine blades in achieving high output power and to evaluate the performance in harnessing wind and solar energy and the continuity to sustainable power generation. This project is quite unique because it was created in one entity to attract two different inputs, namely wind and sunlight to produce DC electricity as output. Wind converts kinetic energy into rotational energy, which is then transferred to a generator via a shaft, generating electrical energy. Solar panels replace rotating blades with PV cells, which absorb sun energy, generating electrical charges that react with internal electrical fields, resulting in electricity flow. This study analyses the value of voltage and current produced by both sources to ensure the level of solar efficiency in generating electricity when the turbine rotates. The analysis shows parallel data between the two even when the blade is rotating but still has a difference of less or an increase of 0.9V. In conclusion, this project innovatively combines hybrid energy by designing a small-scale wind turbine. It aims to show that this technology can be a feasible, environmentally friendly, and cost-effective solution for the industrial and economic sector.